Influence of Project Initiation on Completion of United Nations Joint Programme on Local Governance Road Rehabilitation Projects - Karuri , Solomon; Karanja, Ann (International Journal of Entrepreneurship and Project Management, 2022)
Purpose: The purpose of this study was to examine the influence of project initiation on completion of United Nations Joint Programme on Local Governance road rehabilitation projects. Methodology: This research study adopted a descriptive cross-sectional survey design. The target population was 250 staff working at UNJPLG road rehabilitation projects. The study population included project engineers, clerk of works, project managers, contractors, supervisors, community leaders, and donors making total of 250 respondents. The research study embraced stratified random sampling method and a sample size of 154 respondents was obtained using the Yamane (1967) formula. The study further used structured questionnaires which consisted of both open-ended and closed-ended questions to collect data from the selected respondents. A pilot study was also conducted to test the validity and reliability of the questionnaires. After data was collected, it was examined for efficiency, clarity and clearness. Coding was done on the basis of the place of the participants. Measurable information was evaluated utilizing Statistical Package for Social Sciences (SPSS Version 21) for Microsoft home windows that included detailed and inferential analysis. Data was presented using chart, frequency tables and pie charts. Findings: The study established that project initiation had a significant influence on completion of road rehabilitation projects by United Nations Joint Programme on Local Governance. Findings indicate that the benefits of the road rehabilitation projects are effectively provided by United Nations Joint Programme on Local Governance which enhances their completion. Moreover, the purpose and objectives of road rehabilitation projects are well outlined by United Nations Joint Programme on Local Governance which improves completion of the road rehabilitation projects. Unique Contribution to Theory, Practice and Policy: United Nations Joint Programme on Local Governance should effectively engage key stakeholders during the scoping stage of any future road rehabilitation projects. The organization should also ensure that all key stakeholders including employees are consulted and involved in drafting any project plan. This is expected to enhance buy-in and reduce resistance during the changes that will take place in the implementation phase. The United Nations Joint Programme on Local Governance should ensure that control procedures are put into place to certify that all activities are monitored as execution progresses. The theories used, that is Stakeholder theory and the Theory of Reasoned Actions were found applicable to this study and can be used by other scholars in studies related to the research topic.